(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: In recent years, solar energy has gained increased attention. The energy from the sun is unlimited and environment friendly. It is useful in decreasing the carbon dioxide emission that comes from the burning of fossil fuels and leads to global warming. Materials and Methods: The tilt angle of a solar panel is an important parameter that affects its performance. This paper provides the tilt angle of solar panels for 90 capital cities in 90 countries in the northern and southern hemispheres. Solar Irradiance Calculator is used to calculate the tilt angles from vertical. Results: The tilt angle for the studied capital cities ranges from 11° to 90° in winter, 41° to 105° in summer and 26° to 90° for year-round. The output results obtained from the calculator are very close to those calculated from equations and agree with previous studies. Conclusions: According to the results of the current work, only the latitude is required to calculate the tilt angle at any location worldwide. These results can be generalized to any location on the earth. The results of this work are expected to give valuable information to the users of solar panels.